Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran - Adeldoost, Yaser; Heydari, Ramin; Miraiez, Esmail; Jalalinasab, Parisa; Asghari, Ramezan (Zootaxa, 2016)
Two new species of Seinura are described and illustrated using both morphological and molecular characters. Seinura persica n. sp. is characterized by having females with a distinct cephalic region, stylet 19.5 (18–20) μm long, four incisures in the lateral fields, position of excretory pore anterior to the base of metacorpus, post-uterine sac 54.8 (50–60) μm long, and an elongate-conoid tail with a shallow depression on the dorsal side ending in a sharply pointed tip. Males have body length of 467 and 592 μm, spicules 15 and 16 μm long with a prominent triangular-shaped rostrum, developed condylus and no cucullus. Seinura hyrcania n. sp. is characterized by having an offset lip region, stylet 21.5 (18–24) μm long, three incisures in the lateral fields, excretory pore anterior to the base of the metacorpus, post-uterine sac 19 (12–25) μm long and conical tail ending in a filiform terminus. Morphological and morphometric diagnostic characters together with molecular data based on partial sequences of SSU and LSU of the ribosomal DNA gene are provided for these new species.